High Expression of Tumor Abnormal Protein Preoperatively Predicts Poor Prognosis of Patients With Esophageal Squamous Cell Carcinoma - Cheng, Yuanjun; Fang, Qianru; Chen, Yongbing; Zang, Guohui; Yao, Jie (Frontiers in Surgery, 2021)
Background: Esophageal squamous cell carcinoma (ESCC) acts as a fatal malignant tumor among human beings, and is marked by late stage diagnosis, frequent recurrence, metastasis, and therapy resistance. Tumor abnormal protein (TAP) plays a crucial role in the development and progression of human cancers. TAP has been identified as a biomarker involved in the progression of stomach and lung cancer. However, the clinical significance of the TAP in ESCC remains largely unclear. Methods: In the present study, TAP detection agent was used to examine the relative level of TAP in 183 cases of ESCC tissues and 183 cases who had normal physical check-up during March 2013 and January 2015 at the ChiZhou People’s Hospital. Results: Our data showed that the expression level of TAP was significantly higher in ESCC tissues compared to cases who had normal physical check-up. Moreover, TAP expression was significantly down-regulated after surgery. In addition, the TAP expression was associated with the gender, smoking, pathologic differentiation, and pN stage, but not with the age, tumor location, surgical type, pT stage and vascular invasion. The increased expression of TAP was significantly associated with poorer 5-year overall survival rate of ESCC patients. Multivariate survival analysis indicated that TAP was an independent prognostic factor for ESCC patients. Conclusion: Taken together, our study suggests that the upregulation of TAP expression plays a promoting role in the malignant progression of ESCC. Thus, TAP is a potential biomarker for ESCC progress and a therapeutic target for ESCC.